A World First: Swansea Bay Tidal lagoon in review. (April 2016) - Waters, Shaun; Aggidis, George
Abstract: Global energy focus is turning more and more towards renewable energy. With legally binding agreements requiring a drastic increase in the percentage of national energy demand created with renewable sources, tidal energy holds an important advantage – predictability. The UK is fortunate, having the greatest potential for this energy in the world, which if exploited, would be able to provide approximately 20% of the national energy demand. The most discussed tidal energy site has been the Severn estuary barrage, with repeated proposals outlined and rejected throughout the last 100 years. The reasons for this refusal were due to both high costs and environmental concerns. However, a new proposal for a tidal lagoon in Swansea Bay has been able to circumnavigate both of these downfalls by reducing both the investment needed and effects to the surrounding environment. Subject to a tidal range of 10.5 m and situated next to a largely populated city with excellent grid connections, Swansea bay is a perfect location. If the lagoon project goes ahead, it would be able to produce a rated output of 320 MW using bulb turbines, powering 155, 000 homes. Being the first tidal lagoon project, what is certain is: the UK and Wales in particular are sending out a strong message regarding renewable energy and it has the whole worlds attention. This paper sets out to bring together current literature regarding the planned Swansea Bay tidal lagoon into one concise document.